Estudo sobre a aprendizagem de pseudopalavras por sinestetas dias da semana, meses do ano e grafema-cor - Souza, Brenda Kessia Arruda de (2020)
The general objective of this dissertation is to experimentally show that the synesthesia variants’ driving mechanisms days of the week-color and months of the year-color are related to numerical and abstract conceptual notions. Synesthesia may be defined as a neurological, non-pathological condition, in which stimuli from one sensory modality trigger additional sensations in another modality or different facets of the same sensory dimension, for example, the letter J might be green for an individual with synesthesia and the word Tuesday might be blue (SIMNER, 2011). Synesthesia is already seen more as a condition than a perception and can, therefore, be investigated as a Psycholinguistic phenomenon (MANKIN et al., 2016; SIMNER, 2007). After interviewing roughly 600 people from the general population, we found 13 synesthetes through two testing sessions using the Synesthesia Battery (sinestesia.ufc.br) adapted to Brazilian Portuguese from the Synesthesia Battery (EAGLEMAN et al., 2007). Based on four theories: (i) the theory of Watson et al. (2014) on synesthesia and learning; (ii) Paivio's (2006) double coding theory on the processing of concrete words; (iii) the semantic map of the brain by Huth et al. (2016) and; (iv) the hypothesis of Ramachandran and Hubbard (2001) on the relationship between synesthesia and numerical representation, we work with the hypothesis that the days of the week and months of the year-color variants driving mechanisms are related to abstract and numerical conceptual notions. We also investigated the conceptual basis of these variants, compared the mechanisms that govern them to those that lead to the grapheme-color variant and investigated mnemonic differences between individuals with and without synesthesia. To investigate our hypotheses, we created a methodology to analyze the learning of conceptualized pseudowords. In the tests exclusive to synesthetes, the dependent variables we analyzed were: (i) probability of pairing; (ii) number of colors; (iii) and consistency of pairings. In the tests performed by all participants, the analyzed measures were: (i) absence of recall on the free recall (ii) error in recalling on the forced recall (yes/no); (iii) absence of recalling in the semantic recall and; (iv) number of attributes included in the semantic recall. When analyzing the data gathered in this study, we did not find a statistically significant effect related to the influence of the type of category on the synesthetic pairing. However, our data suggest that synesthesia variants’ days of the week-color and months of the year-color have a conceptual basis, that there are differences between these variants and the grapheme-color synesthesia and that there are differences between the semantic memory of synesthetes and non-synesthetes.